New Evidence of the Impact of Innovative Capacity on Firm Employment - Héctor Alejandro López; Rosa Yagüe-Perales; Isidre March-Chordá (Administrative Sciences)
The business behavior towards innovation and its impact on the creation of new jobs of 113 firms in the Valencian Community (Spain) were analyzed between 2014 and 2020. The sample included manufacturing, services and trading enterprises; technological and non-technological companies; micro-, small, medium, and large enterprises; and locations across the entire geographical extent of the Valencian Community. The firms were divided into quartiles based on their level of employment growth, linearly correlating this variable with 14 innovation indicators for each of the resulting four groups, reflecting the innovative capacity of these firms. It was found that the factor linked to innovation capacity that most favors or drives business employment creation is co-operation with other companies, as it had a direct and significant relationship with the two highest growth groups (quartiles 4 and 3), with no negative relationship with either of the two lower growth groups (quartiles 2 and 1). This suggests that the public administration should increase efforts to create spaces for the exchange of ideas between companies and organizations to reduce unemployment levels. Overall, this study provides new insights into the subject, and its findings lead to the conclusion that firms with higher innovative capacity create more jobs.